Unveiling gender differences in psychophysiological dynamics: support for a two-dimensional autonomic space approach - Menashri Sinai, Yarden; Ma, Yaopeng X. J.; Abba Daleski, Michal; Gannot, Sharon; Bartsch, Ronny P.; Gordon, Ilanit (Frontiers in Human Neuroscience, 2024)
To date, studies focusing on the connection between psychological functioning and autonomic nervous system (ANS) activity usually adopted the one-dimensional model of autonomic balance, according to which activation of one branch of the ANS is accompanied by an inhibition of the other. However, the sympathetic and parasympathetic branches also activate independently; thus, co-activation and coinhibition may occur, which is demonstrated by a two-dimensional model of ANS activity. Here, we apply such model to assess how markers of the autonomic space relate to several critical psychological constructs: emotional contagion (EC), general anxiety, and positive and negative affect (PA and NA). We also examined gender differences in those psychophysiological relations. In the present study, we analyzed data from 408 healthy students, who underwent a 5-minute group baseline period as part of their participation in several experiments and completed self-reported questionnaires. Electrocardiogram (ECG), electrodermal activity (EDA), and respiration were recorded. Respiratory sinus arrhythmia (RSA), pre-ejection period (PEP), as well as cardiac autonomic balance (CAB) and regulation (CAR) and crosssystem autonomic balance (CSAB) and regulation (CSAR), were calculated. Notably, two-dimensional models were more suitable for predicting and describing most psychological constructs. Gender differences were found in psychological and physiological aspects as well as in psychophysiological relations. Women's EC scores were negatively correlated with sympathetic activity and positively linked to parasympathetic dominance. Men's PA and NA scores were positively associated with sympathetic activity. PA in men also had a positive link to an overall activation of the ANS, and a negative link to parasympathetic dominance.